Current global iodine status and progress over the last decade towards the elimination of iodine deficiency - Maria Andersson; Bahi Takkouche; Ines Egli; Henrietta E. Allen; Bruno de Benoist (The World Health Organization, 2005)
OBJECTIVE: To estimate worldwide iodine nutrition and monitor country progress towards sustained elimination of iodine deficiency disorders. METHODS: Cross-sectional data on urinary iodine (UI) and total goitre prevalence (TGP) in school-age children from 1993-2003 compiled in the WHO Global Database on Iodine Deficiency were analysed. The median UI was used to classify countries according to the public health significance of their iodine nutrition status. Estimates of the global and regional populations with insufficient iodine intake were based on the proportion of each country's population with UI below 100 µg/l. TGP was computed for trend analysis over 10 years. FINDINGS: UI data were available for 92.1% of the world's school-age children. Iodine deficiency is still a public health problem in 54 countries. A total of 36.5% (285 million) school-age children were estimated to have an insufficient iodine intake, ranging from 10.1% in the WHO Region of the Americas to 59.9% in the European Region. Extrapolating this prevalence to the general population generated an estimate of nearly two billion individuals with insufficient iodine intake. Iodine intake was more than adequate, or excessive, in 29 countries. Global TGP in the general population was 15.8%. CONCLUSION: Forty-three countries have reached optimal iodine nutrition. Strengthened UI monitoring is required to ensure that salt iodization is having the desired impact, to identify at-risk populations and to ensure sustainable prevention and control of iodine deficiency. Efforts to eliminate iodine deficiency should be maintained and expanded.